Governing failure mode of unsaturated soil slopes under rainwater infiltration - Huang, Wengui (2019)
Due to rainwater infiltration and loss of matric suction above the wetting font, both translational and rotational slips may occur in an unsaturated soil slope. It is useful to know which failure mode is more critical. The governing failure mode is likely to be affected by soil properties, slope geometry, depth of wetting front and contribution of matric suction to shear strength, which were investigated in this study. Specifically, upper bound limit analysis was adopted to develop stability charts based on rotational failure mechanism, and infinite slope model was used to develop stability charts based on translational failure mechanism. For a slope, the failure mechanism which gives the lower factor of safety is the governing failure mode. It was found that the failure mode of an unsaturated soil slope under rainfall is determined by parameter group c′/γHtanϕ′ for a given slope angle, depth of wetting front and contribution of matric suction to shear strength. With the increase in depth of wetting front and greater contribution of matric suction to shear strength, a slope is more prone to translational failure. Slopes with angle β = 45° are most vulnerable to translational failure, while gentler slopes (e.g. β = 15°) and steeper slopes (e.g. β = 75°) are more susceptible to rotational failure.